A thalamic bridge from sensory perception to cognition - Wolff, Mathieu; Morceau, S.; Folkard, Ross; Martín-Cortecero, Jesús; Groh, Alexander (Neuroscience & biobehavioral reviews, 2021)
The ability to adapt to dynamic environments requires tracking multiple signals with variable sensory salience and fluctuating behavioral relevance. This complex process requires integrative crosstalk between sensory and cognitive brain circuits. Functional interactions between cortical and thalamic regions are now considered essential for both sensory perception and cognition but a clear account of the functional link between sensory and cognitive circuits is currently lacking. This review aims to document how thalamic nuclei may effectively act as a bridge allowing to fuse perceptual and cognitive events into meaningful experiences. After highlighting key aspects of thalamocortical circuits such as the classic first-order/higher-order dichotomy, we consider the role of the thalamic reticular nucleus from directed attention to cognition. We next summarize research relying on Pavlovian learning paradigms, showing that both first-order and higher-order thalamic nuclei contribute to associative learning. Finally, we propose that modulator inputs reaching all thalamic nuclei may be critical for integrative purposes when environmental signals are computed. Altogether, the thalamus appears as the bridge linking perception, cognition and possibly affect.
Available online 24 November 2020
Gesehen am 01.04.2021